More tales of the city - Maupin, Armistead 1944- (Harper Perennial, 2014)
The lives of the colorful residents of a San Francisco boarding house are comically intertwined as they search for themselves, their lovers, and families.
Keywords: City and town life -- California -- San Francisco -- Fiction; San Francisco (Calif.) -- Fiction; Humorous fiction